THE VERBAL OF AL- REIB IN SURAH AL IMRAN (ANALYTICAL STUDY) - Duaa Hatam Hadi; Abdullah Ibrahim Rahim Al_ Shammari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The Noble Qur’an is God’s Book, Blessed and Exalted be, given to our Master Muhammad, the Seal of the Prophets and Messengers (peace and blessings be upon him). The Qur’an includes the teachings of God Almighty’s religion, Islam, for people to join with it, create obedience to it, and follow its rules to be happy in this world and the afterlife. Similarly, forcing the obstinate people to argue and persuade them. There is no deity but God, which He is the only one who exists, and Muhammad is His servant and Messenger. In addition, all of the verses in the Noble Qur’an, whether in tales, rulings, morals, or the principles and branches of religion, are united by one principle: to linkman to the unification of God, his allegiance, and his servitude. Given the centrality of the subject of uncertainty in the lives of countries and peoples in this world and the hereafter, we felt it was necessary to offer our thoughts on this important topic. As a result, the title of the study was (The verbal of Al- Reib in Surah Al Imran - Analytical study), and after consulting with experts, I was unable to locate any scholars who had tackled this issue and written about it from an analytical standpoint. Because of the nature of the study on this issue, I had to break it into three sections: an introduction, two chapters, and a conclusion. The reasons for picking the issue, its relevance, and the study plan were all stated in the introduction. The investigations were divided into the following categories: The first point is that God Almighty will assemble His slaves on the Day of Resurrection, and the second is that everyone will be given their right on that day.